Hubungan Kebiasaan Konsumsi Fast Food, Densitas Energi, Zat Gizi Makro dan Mikro Dengan Status Gizi Pada Remaja SMAN 1 Tanjunganom - Sakasiswara, Damara Leylani; Widajati, Endang; Sulistyowati, Etik (NUTRITURE JOURNAL; Vol 3 No 1 (2024): Nutriture JournalDO - 10.31290/nj.v3i1.4058, 2024)
Background : Based on the results of Riskesdas (2018) it shows 25.7% of adolescents aged 13-15 years and 26.9% of adolescents aged 16-18 years with short and very short nutritional status. In addition, there are 8.7% of adolescents aged 13-15 years and 8.1% of adolescents aged 16-18 years who are thin and very thin, while the prevalence of overweight and obesity is 16% in adolescents aged 13-15% years and 13.5% in adolescents aged 16-18 years. Objectives : This study aims to identify the relationship between fast food consumption, energy density, macro and micro nutrients and nutritional status. Methods : The research method uses a statistical analysis using the Chi-Square Test. Determination of the sample based on random sampling method with a total of 65 respondents. Results : The results showed that fast food consumption was often (58.5%), rarely (41.5%). Fast food energy density is low (23%), normal (43%), high (34%). Nutrients consumed by fast food are high energy (60%), high fat (81.5%), high carbohydrates (52.3%), high sodium (87.7%). Conclusion : Based on the research results, it can be concluded that there is a relationship between consumption of fast food, energy density, and macro and micro nutrients with the nutritional status of adolescents (p> 0.05). Recommendation: Advice that can be given is to pay attention to the type and variety of food consumed with a balanced nutritional content according to daily needs.